Food wastes from agrifood industry as possible sources of proteins: A detailed molecular view on the composition of the nitrogen fraction, amino acid profile and racemisation degree of 39 food waste streams. (15th July 2019) - Prandi, Barbara; Faccini, Andrea; Lambertini, Francesca; Bencivenni, Mariangela; Jorba, Montse; Van Droogenbroek, Bart; Bruggeman, Geert; Schöber, Jürgen; Petrusan, Janos; Elst, Kathy; Sforza, Stefano
Highlights: 39 food waste streams of vegetal and dairy origin have been investigated. The nitrogen fraction was deeply characterized at the proteins and amino acid level. Protein amount and quality was assessed in all sources. New sources of high value proteins were identified in still unexploited agro wastes. Abstract: The nitrogen fraction of 39 food waste streams was characterized by Kjeldahl analysis, amino acid analysis, protein analysis and racemization degree, for assessing their potential for further valorization. For every waste streams the specific nitrogen-to-protein conversion factor was calculated, allowing to assess the accurate protein content. The results indicated which streams are most rich in relevant proteins (all wastes of dairy origin, beer yeast, malted barley germs, brewing cake, rapeseed press cake, sea buckthorn spent pulp, leek leaves, parsley waste, pumpkin kernel cake, and mushroom waste), which ones have valuable proteins, but in too little amount, and also which ones are rich in proteins, but of low nutritional value. Specific data also indicated, for every waste stream, its possible use for supplementing specific amino acids. To date, this represents the most complete characterization with homogeneous methodologies of the nitrogen fraction in food waste streams ever reported in the literature and outlines in unprecedented molecular details the potentialities and the limitations of many waste streams to be used as source of proteins.